Identification and biochemical characterisation of an aryl β-glucosidase isolated from a cellulose-acetate rich environment via a functional metagenomic approach - Pieters, Janto (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScAgric)--Stellenbosch University, 2018.